Covid-19 and football: Crisis creates opportunity - Maguire, K. (The Political Quarterly, 2021)
This article looks at the financial performance and position of English professional football before Covid-19 and the impact that the pandemic has had on the industry. It analyses revenue streams in different divisions, the dependency that clubs have on them and how they have changed as a result of the pandemic. The article also reviews key costs for football clubs, the extent to which they can be reduced, different business models that operate, and possible funding sources for the sport from third parties and within the industry.